Scenario Prediction of Provincial Primary Energy Supply under Low Carbon Background: A Case Study of Zhejiang Province - Fan WEN; Jun LIU; Dongxiao NIU; Ze SUN; Yi LIANG; Yao XIAO (Zhongguo dianli)
With the rapid development of China's economy, carbon emissions are increasing and environmental damage is becoming more and more serious. It is of great practical significance and practical value to study the evolution trend of regional energy supply from the perspective of low carbon development. Therefore, Zhejiang Province is used as an example to set three scenarios: routine development scenario, policy development scenario, and technology development scenario for the primary energy supply trend of coal, oil and natural gas. Based on the scenario prediction of low-carbon energy supply in Zhejiang Province by multivariate linear regression models, it can be concluded that low-carbon development will affect the structure of regional energy supply, which is conducive to the planning of primary energy supply in the region.